Development of Learning Media for Grammar A1 with the Theme of Articles in the Dative Case and Prepositions with the Dative Case - Merry Natalia Sidabutar; Indah Aini (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The purpose of this study is to create learning media for A1 grammar subjects on the topic of articles in the dative case and prepositions with the dative case using the Classmarker website. This study uses the Richey and Klein theory model. This includes (i) the planning stage, (ii) the production stage, (iii) the evaluation stage. The data in this study are in the form of words, sentences, phrases, and grammar about articles in the dative case and prepositions with the dative case in the Arbeitsalltag theme. The results of this study are in the form of German language learning media in the form of A1 grammar exercises in the form of quizzes on the theme of articles in the dative case and prepositions with the dative case with the help of the Classmarker website. These exercises consist of 50 questions and use different variations of exercises for each question, such as Multiple choice, Free Text, and Matching. The evaluation results show that this learning media has an overall value of 87.5 (good). This learning media can be accessed online using a laptop and mobile phone.